2006
DOI: 10.5194/nhess-6-315-2006
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and mineralogical heterogeneities of weathered igneous profiles: implications for landslide investigations

Abstract: Abstract. Landslides in tropical and sub-tropical regions are generally associated with weathered rock profiles which often possess chemical and mineralogical heterogeneities at material-and mineral-scales. Such heterogeneities reach a climax by the occurrences of oxyhydroxide-and clayrich zones. Weakness and low permeability of these zones makes them ideal for the development of slip zones along which landslides take place. This paper describes the nature and distribution of chemical and mineralogical heterog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 16 publications
1
14
0
Order By: Relevance
“…al., 2005). Similar observations have been made by Kirk et al, (1997) and are further supported by the fact that the slip zones and detachment surfaces of most landslides in tropical and subtropical settings are partly or completely delineated by persistent heterogeneities (Wen et al, 2004;Duzgoren-Aydin & Aydin, 2006;Aydin 2006 …”
Section: Integrated Aspects For Mabeta Landslide Occurrencesupporting
confidence: 65%
“…al., 2005). Similar observations have been made by Kirk et al, (1997) and are further supported by the fact that the slip zones and detachment surfaces of most landslides in tropical and subtropical settings are partly or completely delineated by persistent heterogeneities (Wen et al, 2004;Duzgoren-Aydin & Aydin, 2006;Aydin 2006 …”
Section: Integrated Aspects For Mabeta Landslide Occurrencesupporting
confidence: 65%
“…The occurrence of landslides in tropical and sub-tropical regions is generally associated with weathered rock profiles characterised by chemical and mineralogical heterogeneities (Duzgoren-Aydin and Aydin, 2006). These weathering profiles develop in response to physical, chemical, and biological processes operating on the earth's surface (Anderson et al, 2002).…”
Section: Introductionmentioning
confidence: 98%
“…The waste water coming from these cities through drains and also transportation of the tannery trough the Gujrat city is the major source of Cr in roadside dust. Aydin et al (2006) reported that elevated level of Cr was due to industrialization but in current study it might be due to tannery industry and its transportation by roads [14]. These are carcinogenic in nature and affects public health [27,11].…”
Section: Discussionmentioning
confidence: 57%